Partnership-defined quality approach to companionship during labour and birth in East New Britain, Papua New Guinea: A mixed-methods study. - Alyce N Wilson; Pele Melepia; Rose Suruka; Priscah Hezeri; Dukduk Kabiu; Delly Babona; Pinip Wapi; Meghan A Bohren; Joshua P Vogel; Angela Kelly-Hanku; Alison Morgan; James G Beeson; et al. (Public Library of Science (PLoS), 2022)
Companionship during labour and birth is a critical component of quality maternal and newborn care, resulting in improved care experiences and better birth outcomes. Little is known about the preferences and experiences of companionship in Papua New Guinea (PNG), and how it can be implemented in a culturally appropriate way. The aim of this study was to describe perspectives and experiences of women, their partners and health providers regarding labour and birth companionship, identify enablers and barriers and develop a framework for implementing this intervention in PNG health facilities. A mixed methods study was conducted with five facilities in East New Britain, PNG. Data included 5 facility audits, 30 labour observations and 29 in-depth interviews with women who had recently given birth, partners and maternity care providers. A conceptual framework was developed drawing on existing quality care implementation frameworks. Women and partners wanted companions to be present, whilst health providers had mixed views. Participants described benefits of companionship including encouragement and physical support for women, better communication and advocacy, improved labour outcomes and assistance with workforce issues. Adequate privacy and space constraints were highlighted as key barriers to address. Of the women observed, only 30% of women had a companion present during labour, and 10% had a companion at birth. A conceptual framework was used to highlight the interconnected inputs required at community, facility and provincial health system levels to improve the quality of care. Key elements to address included attitudes towards companionship, the need for education and training and restrictive hospital policies. Supporting women to have their companion of choice present during labour and birth is critical to improving women's experiences of care and improving the quality of maternal and newborn care. In order to provide companionship during labour and birth in PNG, a complex, intersecting, multi-faceted approach is required.